PERAN BANTUAN HUKUM DALAM MEMBERIKAN BANTUAN HUKUM TERHADAP MASYARAKAT MISKIN DAN MARGINAL - Kadek Mery Heawati; I Gusti Ngurah Aristiawan; Juliana, I Kadek Juliana (Universitas Tabanan, 2023)
The right to legal assistance is a human right for individuals facing legal issues. Legal assistance is a form of access to justice for those involved in legal matters. Obtaining legal aid is also an expression of equality before the law. The provision of legal aid is a human right, especially for the impoverished. In this regard, Legal Aid Institutions (LBH) play a crucial role in advocating for the rights of the poor and underprivileged and enhancing their access to the justice system and other legal services. This research aims to provide insights into the role of legal aid institutions in assisting the poor and marginalized communities. This research is of a normative legal nature, utilizing legislative and analytical approaches to address research questions. Legal aid institutions play a vital role in the application of the law in court, particularly by assisting and/or exercising their authority during investigation and prosecution, aiding in the review process in court, and continuing until the conclusion of cases or the issuance of final judgments.